Bristol UTraQ: A proposed system for scoring the technical quality of urodynamic traces. Issue 2 (15th January 2022) - Gammie, Andrew; Hashim, Hashim; Abrams, Paul
Abstract: Aim: To develop and test a scoring system for the technical quality of a urodynamic trace Methods: Rasch analysis was used to select the most discriminating questions relating to good urodynamic practices. The questions were taken from International Continence Society standard documents and tested on 60 traces of varying quality and from different sources. Results: Twenty‐five questions were selected by this process. These were tested with 10 traces by seven scorers, and with 60 traces by a single scorer. A pass quality score of 75% resulted in good discrimination between good and poor traces. Further editing and clarification resulted in a final score sheet of 23 Yes/No questions. Conclusion: A proposed scoring system, "Bristol UTraQ, " for the technical quality of urodynamic traces has been developed and tested. We suggest a score above 75% indicates acceptable trace technical quality. High technical quality is the essential first step in ensuring that urodynamic studies can answer the urodynamic questions for every patient. Plans for further validation are outlined.